Deep learning-based subtyping of gastric cancer histology predicts clinical outcome: a multi-institutional retrospective study: original article - Veldhuizen, Gregory Patrick; Röcken, Christoph; Behrens, Hans-Michael; Cifci, Didem; Muti, Hannah Sophie; Yoshikawa, Takaki; Arai, Tomio; Oshima, Takashi; Tan, Patrick; Ebert, Matthias; Pearson, Alexander T.; Calderaro, Julien; et al. (Gastric cancer, 2023)
The Laurén classification is widely used for Gastric Cancer (GC) histology subtyping. However, this classification is prone to interobserver variability and its prognostic value remains controversial. Deep Learning (DL)-based assessment of hematoxylin and eosin (H&E) stained slides is a potentially useful tool to provide an additional layer of clinically relevant information, but has not been systematically assessed in GC.